Central Venous Catheterization Complication: Delayed Diagnosis of Venous Perforation and Hemothorax - Murat Bağcı; Hacer Yeter; Aydın Fırıncıoğlu; Kerem Erkalp; Ayşin Alagöl (Galenos Yayinevi, 2015)
Mechanical complications of central venous catheterization (CVC) include artery puncture, vein injuries, catheter malposition (CM), pneumothorax, hemothorax, air embolism, subcutaneous hematoma and arrhythmia. This report was aimed to present the case developing hemothorax due to multilumen catheter (MLC) malposition following venous perforation which is overlooked during CVC. A 21-year old female patient was planned urgent surgery due to a sharp object injury on the right arm. MLC was inserted to left internal jugular vein (IJV) using the seldinger technique in the second attempt. Despite administration of erythrocyte suspension, fluid and noradrenaline infusion through the MLC, patient's Hct did not increase, hypotension and tachycardia were continued. Catheter was not used and peripheral venous vascular access was used for replacement and infusions. Postoperatively, opacity covering the left hemithorax was detected on the chest radiograph, marked pleural effusion and pneumothorax on the left side was detected on thorax computed tomography. MLC was removed and tube thoracostomy drainage was administered. Hemorrhagic fluid was drained from thorax. Conservative treatment was deemed appropriate since stable vital signs after chest tube application. The complication rate is low and success rate is high in CVC from IJV. Malposition is rare in CVC application from right IJV than in CVC application from left IJV. There is a sharp curve in CVC from the left IJV, which frequently leads to malposition of the MLC. CM should be suspected with no aspiration of blood through catheter or aspiration of another substance such as air, chylous fluid, etc. and non-pulsatile blood flow. If dyspnea, tachycardia, tachypnea, hypotension and desaturation develop after catheter administration we should be alert.